Report on the Scottish and English Coins in the Society's Museum (Proceedings of the Society of Antiquaries of Scotland, 1862)
An account of the Scottish and English coins in the Society's collections, including the monarch depicted on each coin and their denominations. Meeting notes for 28 January, 1861 and 11 February, 1861 are appended. The January meeting was a Special Meeting and Conversazione at which Professor J Y Simpson gave his Inaugural Address (see pp5-55).